Monolayers of silver nanoparticles obtained by chemical reduction methods. Issue 3 (1st September 2014) - Adamczyk, Zbigniew; Oćwieja, Magdalena
Abstract : Charge-stabilized silver particle suspensions were prepared by the chemical reduction of silver nitrate using various organic and inorganic reducing agents such as gallic acid, tannin, hydroxylamine hydrochloride, hypophospite, sodium hexametaphosphate, borohydride and trisodium citrate. The control of the size of nanoparticles was achieved by varying the stoichiometric ratio of reagents, resulting in monodisperse nanoparticles with the diameter in the range of 13–17 nm. Surface properties of obtained nanoparticles were determined by electrophoretic measurements over a wide range of ionic strength and pH. Knowing the mobility and size of particles, their effective electrokinetic charge and 2D electrokinetic charge densities were calculated. It was also confirmed by dynamic light scattering measurements that these sols were stable for ionic strength up to 0·03 M, and in the case of tannin, up to 0·1 M. Using these negatively charged suspensions, monolayers of silver particles on poly(allylamine hydrochloride)-covered mica were prepared by a diffusion controlled self-assembly process. The kinetics of monolayer formation was quantitatively determined by atomic force microscopy and scanning electron microscopy imaging of deposited nanoparticles. These experimental results were interpreted in terms of the theoretical modeling based on the random sequential adsorption approach.